The Effect of Driving License (SIM) Services Through the Satpas Electronic Application (E-SATPAS) on Community Satisfaction for Increasing Driving License Production at the Bogor Police During the Covid-19 Pandemic - Rangga Nurrizaldy (Advances in Police Science Research Journal, 2021)
The background of this research was based on the phenomenon of the significant decrease in the number of driver’s license (SIM) production at Bogor Police Station in 2017 until 2020 during the Covid-19 pandemic. Based on data from BPS Bogor Regency and Bogor Traffic Police, the in-crease in population and the number of motorized vehicles is not propor-tional to the number of SIM issuance. The police effort is to provide regis-tration and identification services for motorized vehicles in accordance with PERKAP Number 9 of 2012 regarding SIM, that is the implementation of the Satpas electronic program which will assist SIM issuance services, especially in the Covid-19 pandemic period. This research was aims to describe the impact of driver license (SIM) service implementation through E-Satpas, determine the factors that cause the decrease of public interest in managing driver licenses, and recommend efforts to optimize E-Satpas in increasing SIM production during the Covid-19 pandemic. This research used a mixed-method approach with quantitative research population are the public of driver license applicants in Bogor Police, technically filling out purposive sampling questionnaires is used by taking 94 respondents of new driver license applicants while qualitative research subjects are selected purposively key figure from driver license service officers in Bogor Police by conducting data retrieval conducted triangulate (observation, in-depth interviews, and documentation) equipped with directed group discussions. The result of this research showed that the implementation of driver license services positively impacted the satisfaction level of driver license applicants, which show in the equation of regression y = 14.585 + 0,570x with the effect was 45,7%. The impact is significant, but the contribution is not too big. Based on the results of this research, the writer recommends conclusions and suggestions to increase socialization through social media to reach the public more massively, increase the motivation of officers, add facilities for the Satpas’s prototype building, and increase the inherent supervision by Division of Profession And Security during the SIM exam.